Properties of Nanostructure Bismuth Telluride Thin Films Using Thermal Evaporation - Swati Arora; Vivek Jaimini; Subodh Srivastava; Y. K. Vijay (Journal of Nanotechnology)
Bismuth telluride has high thermoelectric performance at room temperature; in present work, various nanostructure thin films of bismuth telluride were fabricated on silicon substrates at room temperature using thermal evaporation method. Tellurium (Te) and bismuth (Bi) were deposited on silicon substrate in different ratio of thickness. These films were annealed at 50°C and 100°C. After heat treatment, the thin films attained the semiconductor nature. Samples were studied by X-ray diffraction (XRD) and scanning electron microscopy (SEM) to show granular growth.